Recent Developments in the Understanding and Treatment of Neurodegenerative Disorders Involving Protein Conformational Misfolding and Amyloid Formation - Thompson, A. J.; Barrow, C. J. (Medicinal Chemistry Reviews - Online (Discontinued), 2005)
Conformational disease represents an intriguing but devastating class of neurodegenerative disorders that includes prion disease, Alzheimer's disease, Parkinson's disease and Huntington's disease. Although symptoms, on-set times and prognosis among the diseases can vary markedly, the deposition of neurotoxic protein aggregates is a significant commonality, and as such is an attractive therapeutic target. Understanding the mechanisms of protein misfolding and deposition in these conditions is critical to developing effective diagnostic and therapeutic agents. This review serves as an update for the sister publication “Protein Conformational Misfolding and Amyloid Formation: Characteristics of a New Class of Disorders that Include Alzheimer's and Prion Diseases” in Curr. Med. Chem. 2002, 9, 1751-62, and focuses primarily on recent developments in understanding prion disease and Alzheimer's disease in context with other conformational disease. New research in amyloid-related therapeutic strategies is also discussed.
Keywords: amyloid